(untitled) (Universal International Scientific Journal, 2026)
This article examines the importance of pedagogical expertise in the training of highly qualified engineering professionals. It emphasizes the importance of combining a teacher’s deep subject matter expertise with modern teaching technologies and an active approach to delivering materials. Key components of pedagogical expertise are examined, including professional competence, methodological mastery, psychological and pedagogical knowledge, and cultural awareness. The advantages of interactive learning platforms, which enhance learning and develop the necessary skills for successful engineering careers, are described. The need to integrate innovative approaches and active student participation in the educational process is substantiated, and the importance of soft skills alongside professional competencies is emphasized. The conclusion highlights the leading role of pedagogical technologies in developing a comprehensively trained engineering professional prepared to meet the challenges of the modern professional world.